Hungarian Monitoring, 21 September 1988 . [Magyar rádiófigyelő], 1988. szeptember 21 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - State of emergency and curfew in Karabakh hill region - Political forces in the Polish reform process Domestic Affairs: - Government and trade union representatives in talks - Young Communist League (KISZ) Central Committee welcomes formation of Hungarian Democratic Forum (MDF) and New March Front - Romanian village destructions - Austrian industrialists' association and affected parties protest against possible calling off of Gabčíkovo-Nagymaros construction works - Hungarian church leaders support creation of law on right to assemble and associate - Old social democrats also hold speeches at TIT debates: Szabó, Vásárhelyi, Bihari, Révész, Litván, Nyers - Interview with György Faludy present at opening of Sándor Püski's bookshop Economy: - Modifying the tax law - Draft bill on companies - Chamber of Commerce briefing on underperforming economy - Fate of the Ózd Metalworks Külpolitika: - Rendkívüli állapot és kijárási tilalom a Karabah-hegyvidéken - Politikai erők a lengyel reformfolyamatban Belpolitika: - A kormány és a szakszervezetek képviselőinek tárgyalása - A KISZ KB üdvözli az MDF és az Új Márciusi Front megalakulását - A romániai falurombolás témája - Az osztrák gyáriparos szövetség és az érintett cégek tiltakoznak a bős-nagymarosi építkezések esetleges leállítása ellen - A magyarországi egyházi vezetők támogatják a gyülekezési és egyesülési törvény megalkotását - Régi szociáldemokraták is tartanak előadást a TIT vitasorozatán Szabó, Vásárhelyi, Bihari, Révész, Litván, Nyers - Interjú Faludy Györggyel, aki jelen volt Püski Sándor könyvesboltjának megnyitásán Gazdaság: - Adótörvény módosítás - Gazdasági társaságokról szóló törvényjavaslat - A Gazdasági Kamara tájékoztatója a gazdaság elégtelen teljesítményéről - Az Ózdi Kohászati Üzemek sorsa